Zwitterionic Copolymerization of β‐Butyrolactone with Styrene. Issue 18 (23rd August 2018) - Xiao, Meina; Jiang, Jingxing; Zhang, Tongtong; Xu, Anli; Ke, Zhuofeng; Hong, Liangzhi
Abstract: The hybrid copolymerization of vinyl monomers with cyclic esters endows the formed copolymers new features, such as biodegradability and functionality. However, the recently reported hybrid copolymerizations are mainly based on polar vinyl monomers and cyclic esters catalyzed by organocatalysts. The copolymerization of non‐polar vinyl monomers with cyclic esters is still a challenge. In this work, the copolymerization of β‐butyrolactone (β‐BL) with styrene catalyzed by B(C6 F5 )3 in the absence of coinitiators is reported. The density functional theory studies suggest the formation of zwitterion between β‐BL and B(C6 F5 )3 . It is found that β‐BL and styrene are concurrently copolymerized through the macro‐zwitterion intermediates. The obtained copolymers are carefully examined by 1 H NMR, 2D 1 H‐ 13 C HMBC, differential scanning calorimetry, thermogravimetric analysis, hydrolysis experiments, as well as Brady's reagents. Abstract : Poly(β‐butyrolactone‐ co ‐styrene) copolymers with multi‐block sequences are synthesized from the hybrid copolymerization of β‐butyrolactone with styrene using B(C6 F5 )3 as the catalyst.